2020
DOI: 10.1111/andr.12958
|View full text |Cite
|
Sign up to set email alerts
|

In vitro survival kinetics of microfluidic‐sorted bovine spermatozoa

Abstract: Background The isolation and characterization of sperm subpopulations that can achieve fertilization is a major challenge of assisted reproduction methods. We focused on the microfluidic sperm sorter as a novel tool for collecting highly motile spermatozoa from heterogeneous semen samples. Objectives This study primarily aims to obtain baseline information on sorted spermatozoa according to its characteristics and in vitro life span. Materials and Methods Frozen‐thawed bull semen was subjected to microfluidic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Effective semen cryopreservation is one of the key elements contributing to the success of assisted reproductive technologies (ART) in cattle breeding and human reproductive medicine. Published studies often make comparisons between the ejaculates of different bulls/breeds or between the swim up fractions [ 31 , 42 , 43 ]. While investigating the topic, we have not come across works that would compare bulls with high and low semen evaluation scores.…”
Section: Discussionmentioning
confidence: 99%
“…Effective semen cryopreservation is one of the key elements contributing to the success of assisted reproductive technologies (ART) in cattle breeding and human reproductive medicine. Published studies often make comparisons between the ejaculates of different bulls/breeds or between the swim up fractions [ 31 , 42 , 43 ]. While investigating the topic, we have not come across works that would compare bulls with high and low semen evaluation scores.…”
Section: Discussionmentioning
confidence: 99%
“…Choosing morphologically better quality and motile spermatozoa allows for increased sperm capacitation ability and, as a result, more successful fertilization with oocyte (Mirsanei et al, 2022; Yildiz & Yuksel, 2019). Accordingly, the use of microfluidic sperm sorting devices allows the selection of spermatozoa that are more suitable for in vitro fertilization (Anbari et al, 2021; Asghar et al, 2014; Ogata et al, 2021; Pujol et al, 2022; Quinn et al, 2017). Moreover, Ogata et al (2021) reported that a diffuser‐type microfluidic sperm sorter, a different sperm‐separating device, can select highly motile spermatozoa with the ability to maintain its membrane integrity and mitochondrial function related to ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the use of microfluidic sperm sorting devices allows the selection of spermatozoa that are more suitable for in vitro fertilization (Anbari et al, 2021; Asghar et al, 2014; Ogata et al, 2021; Pujol et al, 2022; Quinn et al, 2017). Moreover, Ogata et al (2021) reported that a diffuser‐type microfluidic sperm sorter, a different sperm‐separating device, can select highly motile spermatozoa with the ability to maintain its membrane integrity and mitochondrial function related to ATP production. Thus, it is thought that the rate of reaching the blastocyst and the quality of the blastocyst may have increased after the selection of better quality and less damaged spermatozoa and successful fertilization of the oocyte and spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…In bovines, more functional and progressively motile spermatozoa with high DNA integrity have been obtained recently (Nagata et al, 2018), based on ability of sperm to cross laminar flow streamlines. Highly motile spermatozoa with intact membrane integrity and mitochondrial function from frozen-thawed bull semen have been successfully sorted using diffuser-type microfluidic sperm sorter (DMSS, Ogata et al, 2021). DMSS is now considered by many as a high-quality sperm selection method to achieve great potential of assisted reproduction in bovines.…”
Section: Introductionmentioning
confidence: 99%